Research and development of production technology for ethnic functional product "red cottage cheese" - Alkhamova Guzel; Lukin Aleksandr (WESSLING Nemzetközi Kutató és Oktató Központ Közhasznú Nonprofit Kft. Budapest, 2020)
The technology of “Red Cottage Cheese” production is deeply rooted in the past of the Turkic people. “Red Cottage Cheese”, with its creamy caramel flavor, has long been considered a delicacy. The Turkic people cooked “Red Cottage Cheese” by a long-term simmering of the mixture of whole milk and a fermentation agent in order to obtain a curd clot, and then adding sugar and butter. The aim of the research is to develop a new technology for the production of the ethnic functional product “Red Cottage Cheese”. To develop this new cottage cheese product, we used skim milk, fermentation agent, and stevioside.
Keywords: Műszaki és technológiai tudományok; Egyéb műszaki tudományok és technológiák; Élelmiszer és italfélék